Sinonasal renal cell-like adenocarcinoma, a unique variant of primary clear cell carcinoma of the head and neck: The first reported case in Korea. Issue 31 (August 2017) - Kim, Nah-Ihm; Yang, Jung-In; Kim, Sung-Sun; Lee, Ji-Shin; Lim, Sang-Chul; Jung, Shin; Lee, Jae-Hyuk; Moon, Kyung-Sub; Lee, Kyung-Hwa
Abstract: Rationale: Primary sinonasal renal cell-like adenocarcinoma (SNRCLA) is a rare and unique neoplasm. Patient concerns: A 63-year-old man presented with repeated epistaxis, nasal obstruction and hyposmia of 2-month duration. Radiological studies revealed a mass of the left ethmoid sinus involving anterior skull base. Diagnosis: The patient was treated with craniofacial resection, bifrontal craniotomy combined with an endonasal endoscopic approach. Intraoperatively, a hypervascular paranasal mass invading the dura mater was removed en block . Histologically, the tumor resembled a clear cell renal cell carcinoma, with cuboidal shaped cells having clear cytoplasm. The tumor cells were positive for CK7, S100, vimentin and PAX-8 and negative for CD10 and PAX-2 by immunohistochemistry. No evidence of renal malignancy was found by radiological and clinical examinations. Interventions and outcomes: Following local radiation therapy, the patient was in good health without recurrence for 15 months after the operation. Lessons: To the best of the authors' knowledge, this is the first reported case of SNRCLA in Korea. Because of its histological feature of clear cytoplasm, SNRCLA needs to be differentiated from clear cell renal cell carcinoma and other salivary clear cell carcinomas. The prognosis of SNRCLA is generally favorable as shown in the previously reported cases. Considering the limited number and follow-up periods of the cases, however, delayed recurrence should be kept in mind for clinicians.